Dilemmas of educational ethics : cases and commentaries - Levinson, Meira (Harvard Education Press, 2016)
"Dilemmas of Educational Ethics introduces a new interdisciplinary approach to achieving practical wisdom in education, one that honors the complexities inherent in educational decision making and encourages open discussion of the values and principals we should collectively be trying to realize in educational policy and practice"--